Triceps skinfold-albumin index predicts overall survival of malignant tumors in at least two organs: a multicentre cohort study - Feifei Chong; Zhenyu Huo; Ning Tong; Xin Lin; Na Li; Siyu Luo; Li Wang; Hongxia Xu (Holistic Integrative Oncology)
Abstract Background The present study evaluated the prognostic value of a new published joint index, the fat mass triceps skinfold-albumin index (TA) in patients with malignant tumors in at least two organs (MTT). Methods Patients for this study were recruited prospectively as part of a multi-center cohort study titled "Investigation on Nutrition Status and its Clinical Outcome of Common Cancers in China" (INSCOC), conducted between January 2013 and December 2019. The study focused on MTT patients. The time-dependent receiver operating characteristic (ROC) curve analysis was employed to assess and compare the predictive accuracy of various nutritional and inflammatory indices, including the triceps skinfold-albumin index (TA), handgrip strength (HGS), midarm circumference (MAC), calf circumference (CC), systemic immune-inflammation index (SII), patient-generated subjective global assessment (PG-SGA), and malnutrition identified by the Global Leadership Initiative on Malnutrition (GLIM) criteria. Multiple Cox regression models were utilized to investigate the relationship between TA levels (categorized as continuous or normal vs. low) and overall survival (OS). Survival outcomes were graphically represented using Kaplan–Meier (K-M) curves. Results Five hundred five patients (290 male and 215 female) were included in this study. According to the cut-off of TA (women: 49.9; men: 45.6), 347 patients (68.7%) and 158 patients (31.3%) were categorized as TA normal and TA low, respectively. TA low group had a higher incidence of vomiting than normal group (P = 0.041). The TA low played the negative role in nutrition related index (BMI, MAC, CC, HGS, PG-SGA score and malnutrition diagnosed by GLIM) (all P < 0.001). The curve of TA has been consistently above other curves (HGS, MAC, CC, SII and GLIM-defined malnutrition). After adjusted for age, gender, smoking, alcohol and other different variables, TA (normal vs low) is an indicator in predicting the survival of MTT patients in 4 models (model 1: HR = 0.588, 95% CI:0.432, 0.801; model 2: HR = 0.600, 95% CI: 0.435, 0.827; model 3: HR = 0.597, 95% CI: 0.433, 0.823; model 4: HR = 0.582, 95% CI: 0.380,0.892). Conclusion This study evaluated the prognostic index of the TA in MMT patients, which may direct the nutritional intervention strategies to improve the clinical outcomes, including overall survival.